Модернізація комплексу типу ІК-1У для вимірювання опору заземлювального пристрою блискавковідводів та опор ЛЕП - Коліушко, Денис Георгійович; Руденко, Сергій Сергійович; Плічко, Андрій Валерійович; Щербінін, В. І. (Національний технічний університет "Харківський політехнічний інститут", 2019)
Метою роботи є створення вимірювального приладу для визначення опору заземлювальних пристроїв (ЗП) блискавковідводів та опор повітряних ліній електропередачі(ЛЕП) при дії аперіодичних імпульсів напруги з параметрами 1,2/50 мкс та струму з параметрами8/20 мкс і10/350 мкс. Для цього використано теорію електротехніки, програмні засоби моделювання перехідних процесів та методи натурного моделювання. Було визначено параметри елементів електричного кола додаткового формуючого блоку для створення грозових імпульсів струму з параметрами 10/350 мкс за допомогою вимірювального комплексу типу ІК-1У. Вдосконалено комплекс типу ІК-1У, що дозволило визначати імпульсний опір ЗП блискавковідводів та опор ЛЕП при дії імпульсів струму10/350 мкс, 8/20 мкс та напруги 1,2/50 мкс. Модернізований прилад дозволяє проводити вимірювання відповідно з сучасними міжнародними вимогами.

Purpose.The creation of a measuring device for determining the impedance of the grounding of lightning arresters and supports of overhead lines under the influence of aperiodic pulses with the parameters 1.2/50 μs, 8/20 μs and 10/350 μs. Methodology. For this purpose, electrical engineering theory, transient modeling software and natural modeling methods are used. Results. The parameters of the electrical circuits of the additional forming unit were determined to create lightning current pulses with parameters of 10/350 μs using the IK-1U measuring complex. According to the simulation results, a layout of the forming unit in the form of an attachment and the IK-1U complex with the upgraded power supply system were created. Oscillograms of the front and pulse duration are obtained. The specified model was tested when performing electromagnetic diagnostics of the state of the RFP for more than 100 operating electrical substations. Originality. The measuring complex IK-1U was improved, which made it possible to determine the impulse impedance of the grounding device of lightning arresters when exposed to a current of 10/350 μs, 8/20 μs and of voltages 1.2/50 μs. Practical value.Upgraded device allows measurements in accordance with modern international requirements.
Modernization of the complex type IK-1U for measuring the impedance of the grounding device of a lightning arrester and supports of transmission lines
Keywords: опір; грозовий імпульс струму (напруги); вимірювальний комплекс; impedance; lightning current (voltage) pulse; measuring complex